Biochemical Analysis of 25 Genotypes of Grain Amaranths (Amaranthus Hypochondriacus L.) (Global Journal of Science Frontier Research, 2012)
such as Cholrophylls (a & b), Carotenoids, Protein, Vitamin C, Phenol, Niacin, Vitamin B1, Vitamin B2, Moisture analysis for 25 genotypes of Amaranthus hypochondriacus
Keywords: Amaranthus hypochondriacus; Biochemicals; Chlorophyll; Vitamins